What Makes an Ideal Chairperson? Organizational Members’ Perspectives on Leadership Attitude - Muhammad Dzimar; Putri Amalia Salsabila; Lita Nala Khisymah (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2025)
Leadership plays a vital role in shaping the effectiveness of student organizations as platforms for developing future leaders. However, limited attention has been given to the specific leadership attitudes expected by members toward their organizational chairperson in non-formal educational settings. This study aims to identify the ideal leadership attitudes perceived by members of student organizations at the Faculty of Education and Teacher Training, UIN K.H. Abdurrahman Wahid Pekalongan. Using a descriptive qualitative approach, data were collected through semi-structured interviews with sixteen participants from six organizations and were analyzed thematically. The findings reveal five key attitudes communicativeness, critical thinking, assertiveness, inclusiveness and responsibility, and motivation as essential elements of ideal leadership. These results suggest that effective leadership in student organizations requires not only managerial competence but also empathy, emotional intelligence, and consistency. The study recommends integrating these attitudes into leadership development programs to foster inclusive, reflective, and empowering leadership behaviors that enhance organizational harmony and member motivation.